Tepung Tawar Sebagai Modal Sosial dalam Mendamaikan Sengketa: Kearifan Lokal dalam Naskah Ulu dan Keberlangsungannya - Izzuddin, Muhammad Haidar; Afriansyah, Syafran (Jumantara: Jurnal Manuskrip Nusantara, 2025)
This research examines the role of the tradition of tepung tawar, particularly in the Ulu manuscript 93 E 1 in the National Library of the Republic of Indonesia, as social capital in resolving conflicts and reconciling disputes. Social conflicts, especially in social relations, are increasing in a competitive modern society. As a nation rich in local wisdom values, Indonesia has great potential to resolve conflicts peacefully by utilizing traditional wisdom. One of the local traditions that can be used as social capital is the tepung tawar tradition. This research has two main objectives, namely to reveal the content of Ulu manuscript 93 E 1 related to the tepung tawar tradition and to analyze its relevance to the practice of tepung tawar in reconciling conflicts in modern society. To achieve these objectives, a descriptive qualitative method is used to document and analyze the Jampi Tepung text in the manuscript. This approach involves an in-depth text study by identifying key elements of the rituals and prayers contained in the manuscript. Additionally, social capital theory by sosial Colletta dan Cullen (2000)  and restorative justice by Braithwaite (2002) are applied to link the local wisdom of the tepung tawar tradition with contemporary conflict resolution practices. The findings of this study show that Ulu 93 E 1 contains important information about the tradition of fresh flour. This tradition, although rooted in local wisdom, remains relevant and can become social capital in a modern context to achieve social harmony.